Ehrenfest en Einstein. Menselijke katalysator van het heldere denken - Hollestelle, Marijn (Studium, 2016)
Ehrenfest and EinsteinEhrenfest and Einstein met just before Ehrenfest became professor at Leiden University. They had much in common and became best friends. Ehrenfest shed light on some problematic aspects of Einstein’s work and during the years acted as an important sparring partner for Einstein. Ehrenfest also explained difficult aspects of Einstein’s work to the physics community. He set others on the track of working on general relativity and made Leiden an international centre for these developments during the years 1912–1920. Ehrenfest made sure Einstein was appointed part-time professor at Leiden, from which Leiden physics profited. He also aided Bohr and Einstein during their notorious debates. Ehrenfest struggled with depression his whole life. The rapid developments and mathematicising of quantum physics, Hitler’s appointment as Reichs Chancellor, money and marriage problems worsened his depressions. In 1933 Ehrenfest committed suicide, and Einstein moved to the United States and away from the study on quantum physics.